1118. Viral Species Richness and Composition in Young Children With Loose or Watery Stool in Ethiopia. (26th November 2018) - Aiemjoy, Kristen; Altan, Eda; Aragie, Solomon; Fry, Dionna; Phan, Tung; Deng, Xutao; Chanyalew, Melsew; Tadesse, Zerihun; Callahan, Kelly; Delwart, Eric; Keenan, Jeremy
Abstract: Background: Stool consistency is an important diagnostic criterion in both research and clinical medicine and is often used to define diarrheal disease. Methods: We examine the pediatric enteric virome across stool consistency to evaluate differences in richness and community composition using fecal samples collected from children participating in a clinical trial in the Amhara region of Ethiopia. The consistency of each sample was graded according to the modified Bristol Stool Form Scale for children (mBSFS-C) before a portion of stool was preserved for viral metagenomic analysis. Stool samples were grouped into 29 pools according to stool consistency type. Differential abundance was determined using negative-binomial modeling. Results: Of 446 censused children who were eligible to participate, 317 presented for the study visit examination and 269 provided stool samples. The mean age of children with stool samples was 2.7 years old. Species richness was highest in watery-consistency stool and decreased as stool consistency became firmer (Spearman's r = −0.45, P = 0.013).The greatest differential abundance comparing loose or watery to formed stool was for norovirus GII (7.64, 95% CI 5.8, 9.5) followed by aichivirus A (5.93, 95% CI 4.0, 7.89) and adeno-associated virus 2 (5.81, 95% CI 3.9, 7.7). Conclusion: We documented a difference in pediatric enteric viromes according to mBSFS-C stool consistency category, both in species richness and composition. Our results suggest that loose or watery stool, as measured by the mBSFS-C, may signal enteric viral infection in young children. Additional studies are warranted to confirm these findings. Disclosures: All authors: No reported disclosures.